REVIEW OF THE RESEARCH IN CROP WATER REQUIREMENT AND ITS USE IN THE REPUBLIC OF MACEDONIA - Chukaliev, Ordan (Macedonian Academy of Sciences and Arts, 2017)
The paper presents a review of the research activities dealing with evapotranspiration (ET), crop water re-quirement (CWR) and the use of these parameters in other research, particularly in climate change. The first part dis-cusses the development of these research methodologies globally. Later the achievements of the national research are discussed. Macedonia did not developed capacities for measuring of the ET and the crop water requirement. There is only one practice which is followed – field experiments for the assessment of the water balance with bucket approach. The estimation of evapotranspiration is based mainly on the Penman – Monteith FAO 56 procedure. Due to the lack of input data the less data intensive Thornthwhaite methodology is applied. In the country the ET and the crop water requirement are used in irrigation projects, in research activities and in the assessment of the effects of water limita-tion on crop yield, particularly in climate change. Recently some activities dealing with the use of crop biophysical models WOFOST and CropSyst are taken.